La Política de apertura de datos abiertos aplicada a la data registral y la seguridad jurídica en las transacciones inmobiliarias - Aguirre Sigueñas, Luz Génesis (2018)
Currently, information is of crucial importance in commercial transactions, especially in the legal traffic of goods. Thus, in the contractual world, there will always be a better informed subject, who is usually the seller, thus originating the great problem of informational asymmetry and consequently the violation of legal security. Taking into account this sequence, there is a public entity, whose main function is to eliminate the informational asymmetry between the contracting parties in all the legal dimensions in which it operates. (CINDER I., 2014): The National Superintendency of Public Registries -SUNARP. And being the State in charge of organizing and administering the registration and advertising registration services, one might wonder if the policy of opening open data applied to the information held by the Public Registries reinforces the legal security in real estate traffic. Delimiting several questions such as What data can be public and what data, no? What happens with personal data? What could be the criterion to say that a registration data is reusable by a citizen? Would the innovation of new services or products be encouraged with the registration information provided? to all this, the computerized processing of the data and the application of the TICs for it, although it is not essential for the fulfillment of the essential function of the Registry of the Property, allows to achieve greater efficiency in the provision of the service. Although the topic is very broad, our purpose is to outline certain answers to the questions raised, in order to formulate a position inclined to the application of data policy open to the registry data as a strengthening of legal security in the transaction of real estate.